PENGEMBANGAN PRODUK PERBANKAN SYARI’AH DI INDONESIA: Sebuah Upaya Mengantisipasi Kebutuhan Pasar - Ulum, Fahrur (el-Qist : Journal of Islamic Economics and Business (JIEB), 2012)
Along with the development of the Islamic banking in Indonesia, the need for the development of its products is also increasing and demanding. This is of course aimed to fulfil the Islamic banking market that needs such products. The development of the Islamic banking products must be in line with the market need as well as in accordance with shariah principle and in the form of Fatwa that is produced by National Shariah Council (Dewan Syariah Nasional). Up to now, there are a few Fatwa regarding the products which are constrained to be applied and implemented in the market. There are fatwa regarding saving and deposit and financing or channeling fund and fatwa regarding treasury that must be produced sooner. In short, Product innovation that is able to penetrate the market need as well as in accordance with shariah principle absolutely needed for the Islamic banking to increase its competitiveness domestically, regionally and globally in the era of free market competition and along with the opportunities and challenges.